Evaluation of content knowledge and instructor impacts in a middle school outreach program: lessons from Brain Explorers - Vollbrecht, Peter J.; Cooper, Carolyn E. A.; Magoline, Joseph A.; Chan, Thomas M.; Porter-Stransky, Kirsten A. (Frontiers in Education, 2024)
Despite general agreement that science outreach is important, the effectiveness of science outreach programs on participants' learning often is not assessed. Brain Explorers is a neuroscience outreach program that allows medical students to partner with Biomedical Sciences faculty to develop lesson plans with learning objectives, interactive experiments for middle schoolers, and assessments of learning. These lessons are then implemented through a community-level intervention in which medical students teach their lesson plans to middle schoolers and assist them in performing activities to reinforce the concepts. Importantly, the efficacy of these active learning interventions is assessed. Throughout the program's evolution, a variety of different forms of assessment have been utilized to examine student understanding. While the goals of outreach programs are varied, here we have focused on the evaluation of content knowledge gains laying out three unique evaluation methods including post-event, immediate pre-and post-event, and spaced pre-and post-event evaluation. Specifically, using Brain Explorers lessons as examples we explore the practicality and feasibility of various learning assessments in outreach programs, begin to examine the impacts of participation in these programs on the medical school instructors and encourage others in the field to implement assessment of their programs.